Surface adsorption of hydroxyapatite nanoparticles with catechol modified hyaluronic acid - Ataalp, Nihan (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2016., 2016)
Biopolyelectrolytes have been a very popular research field due to their applications ranging from food science to biomaterials. Biopolyelectrolytes can bind with higher affinity to the surfaces of biodevices if their structure is modified with various chemical groups. In the long term, the goal here was to prepare artifical bone. In the short term, our goal was to prepare systems where biopolyelectrolytes are adsorbed onto hydroxyapatite nanoparticles. In this study, at the first step, the effects of 2-carboxyethyl phosphonic acid (CEPA) and citrate on the synthesis of hydroxyapatite nanoparticles were investigated. In another method, hydroxapatite nanoparticles were synthesized while controlling crystallinity. In the next step, hydroxyapatite adsorption of polyacrylic acid (PAA), unfunctionalized HYA (hyaluronic acid) and catechol functionalized HYA were compared. Fourier Transform Infrared spectroscopy (FTIR) and thermogravity analysis (TGA) were applied to characterize the samples. According to the TGA characterization results, the highest level of surface modification on hydroxyapatite nanoparticles (3.25 %) was found for catechol functionalized hyaluronic acid (234 kDa).
Keywords: Nanoparticles.; Polyelectrolytes -- Biotechnology.